2018
DOI: 10.1016/j.scitotenv.2017.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Use of multi-criteria decision analysis to identify potentially dangerous glacial lakes

Abstract: Glacial Lake Outburst Floods (GLOFs) represent a significant threat in deglaciating environments, necessitating the development of GLOF hazard and risk assessment procedures. Here, we outline a Multi-Criteria Decision Analysis (MCDA) approach that can be used to rapidly identify potentially dangerous lakes in regions without existing tailored GLOF risk assessments, where a range of glacial lake types exist, and where field data are sparse or non-existent. Our MCDA model (1) is desk-based and uses freely and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 73 publications
0
46
0
1
Order By: Relevance
“…Individual reviews of these selected aspects of GLOF research have been elaborated, e.g. by Huggel et al (2002) and Quincey et al (2005), focusing on the application of remotely sensed data, and by Kougkoulos et al (2018), focusing on GLOF susceptibility assessment (see also Sect. 4.3).…”
Section: Analysis Of the Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual reviews of these selected aspects of GLOF research have been elaborated, e.g. by Huggel et al (2002) and Quincey et al (2005), focusing on the application of remotely sensed data, and by Kougkoulos et al (2018), focusing on GLOF susceptibility assessment (see also Sect. 4.3).…”
Section: Analysis Of the Contentmentioning
confidence: 99%
“…3.3). While hazard (susceptibility) assessment is traditionally dominant in GLOF risk studies (see the overview of methods by Kougkoulos et al, 2018), vulnerability assessment and adaptation in the broader context of retreating glaciers and water resources still remain brand new topics, which need to be further addressed in most regions and especially those located in developing countries (e.g. Vuille et al, 2018).…”
Section: Challenges Ahead and Research Directionsmentioning
confidence: 99%
“…1). The three lakes identified by Kougkoulos et al (2018) as having the highest risk include Laguna Arkhata, Pelechuco Lake, and Laguna Glaciar (Fig. 1).…”
Section: Geographical Settingmentioning
confidence: 99%
“…They undertook a rudimentary assessment of GLOF risk in the region, suggesting that 25 lakes could pose a risk to downstream communities. Subsequent work by Kougkoulos et al (2018) developed a GLOF risk assessment technique based on the use of multicriteria decision analysis (MCDA), which was applied to the lake inventory of Cook et al (2016). Kougkoulos et al (2018) found that two lakes represented 'medium' risk and one lake represented 'high' risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation